Association of ABO Blood Types and Clinicopathological Features of Prostate Cancer. (9th October 2017) - Wang, Fang-Ming; Zhang, Yan; Zhang, Gui-Ming; Liu, Ya-Nan; Sun, Li-Jiang; Liu, Yong
Abstract : Purpose . To investigate the association between ABO blood types and clinicopathological characteristics in patients with prostate cancer (PC). Methods . A total of 237 pathologically diagnosed PC patients were enrolled. All patients were classified as low–middle or high-risk group. The correlation of ABO blood types with high-risk PC was determined by univariate and multivariate regression analysis. Results . Data indicated 144 (85.7%) patients were stratified as high risk in the non-O group, while 50 (72.5%) patients in the O group (p = 0.025 ). However, there was no significant difference regarding PSA, Gleason score, stage, or metastasis between O and non-O group (p > 0.05 ). Univariate logistic regression analyses revealed PSA, Gleason score, and blood type non-O were all correlated with high-risk PC (OR = 1.139, p < 0.001 ; OR = 9.465, p < 0.001 ; OR = 2.280, p = 0.018, resp.). In the stepwise multivariate regression analysis, the association between blood type non-O and high-risk PC remained significant (OR = 33.066, 95% CI 2.391–457.323, and p = 0.009 ) after adjusting for confounding factors as well as PSA and Gleason score. Conclusion . The present study firstly demonstrated that non-O blood type was at higher risk of aggressive PC compared with O type, suggesting that PC patients with non-O blood type should receive more attention in clinical practice.